“SOLASTALGIA” AND ECO-ANXIETY IN THE GLOBAL SOUTH: A COMMUNITY-BASED STUDY ON PSYCHOLOGICAL ADAPTATION TO CLIMATE CHANGE - Maarif, Mohammad Syamsul; Lee, Ava; Iqbal, Kiran (World Psychology, 2025)
Psychological research on climate change, dominated by Global North “eco-anxiety,” fails to capture the lived reality of the Global South. This ethnocentric bias overlooks the profound, place-based distress experienced by frontline communities facing immediate environmental degradation. This study aimed to investigate the manifestations of solastalgia and eco-anxiety and identify indigenous psychological adaptation strategies using a community-based participatory approach in the Global South. A Community-Based Participatory Research (CBPR) framework, employing a sequential explanatory mixed-methods design, was implemented in two climate-vulnerable sites (coastal Southeast Asia and agrarian Sahel, N=804). Qualitative methods informed the co-development of the Community Climate Distress and Resilience Scale (CCD-RS). Findings revealed that “solastalgia” (present-tense, place-based grief) is the dominant psychological burden, significantly superseding future-oriented ‘eco-anxiety’. Qualitative analysis identified local idioms of distress (e.g., “the sea is tired”). Resilience was not an individual trait but a collective process, strongly predicted by involvement in community rituals (β = .31, p < .001). The study provides an empirical corrective to the ethnocentric bias in climate psychology, demonstrating that psychological adaptation in the Global South is collective and place-based.